Sites and gene products involved in lambdoid phage DNA packaging. - Smith, M P (1993)
21 is a temperate lambdoid coliphage, and the genes that encode the head proteins of lambda and 21 are descended from a common ancestral bacteriophage. The sequencing of terminase genes 1 and 2 of 21 was completed, along with that of a segment at the right end of 21 DNA that includes the R4 sequence. The R4 sequence, a site that is likely involved in termination of DNA packaging, was found to be very similar to the R4 sequences of lambda and phi 80, suggesting that R4 is a recognition site that is not phage specific. DNA packaging by 21 is dependent on a host protein, integration host factor. A series of mutations in gene 1 (her mutations), which allow integration host factor-independent DNA packaging by 21, were found to be missense changes that affect predicted alpha-helixes in gp1. gp2, the large terminase subunit, is predicted to contain an ATP-binding domain and, perhaps, a second domain important for the cos-cutting activity of terminase. orf1, an open reading frame analogous in position to FI, a lambda gene involved in DNA packaging, shares some sequence identity with FI. orf1 was inactivated with nonsense and insertion mutations; these mutations were found not to affect phage growth. 21 was also not able to complement a lambda FI mutant.